Students’ Perception on the Accuracy and Reliability of Financial Statements Generated by Computerized Accounting Systems in Ugandan Universities - Spencer Ronald Abaho (Uganda Christian University, 2024)
In today's rapidly evolving business environment, organizations increasingly leverage technology to enhance operations and achieve strategic goals, particularly in accounting, where computerized accounting systems (CAS) offer benefits such as enhanced data accuracy, improved efficiency, and real-time financial reporting. This study investigates students' perceptions of the accuracy and reliability of financial statements generated by Computerized Accounting Systems (CAS) in universities. As technology becomes an integral part of financial management, particularly in academic institutions, understanding users' trust in these systems is critical. The study focused on 60 university students and 6 university accounts officers, examining their opinions through a structured questionnaire designed to measure various aspects of CAS, including accuracy, consistency, minimization of errors, and overall reliability. The findings reveal diverse perspectives on the effectiveness of CAS, with many students expressing confidence in its accuracy but also highlighting concerns about occasional discrepancies and the necessity of manual oversight. Overall, this study contributes to the discourse on CAS in universities by highlighting the need for continuous improvement and training to maximize the systems' reliability and accuracy in financial reporting.
Undergraduate research